Strategi Pemberdayaan Kawasan Kumuh di Kota Makassar: Peluang dan Tantangan dalam Pembangunan Berkelanjutan - Dahlan, Mubarak (Research Agency for Humanity and Urban, 2025)
This article aims to identify and analyze the forms of empowerment strategies implemented by the government in urban slums to support the mission of sustainable development as a strategic global issue. This study uses a qualitative approach with a case study model and conducts in-depth interviews with various levels of society involved in this program. The results of the study found that the empowerment of slum areas in the city of Makassar, so far, is not only oriented towards a series of physical improvements such as infrastructure development, but must also involve social, economic, and environmental aspects. Several important recommendations related to strategic steps include increasing community participation, cooperation between the government, the private sector, and NGOs, and strengthening local capacity in natural resource management. Another strategic step is community-based empowerment, with an emphasis on empowering local communities in every stage of project planning and implementation, particularly as an effort to improve the quality of life of residents living in slum areas.